Au⋅⋅⋅H−C Interactions Support a Robust Thermally Activated Delayed Fluorescence (TADF) Gold(I) Complex for OLEDs with Little Efficiency Roll‐Off and Good Stability. Issue 40 (2nd September 2022) - Feng, Xingyu; Yang, Jian‐Gong; Miao, Jingsheng; Zhong, Cheng; Yin, Xiaojun; Li, Nengquan; Wu, Chao; Zhang, Qizheng; Chen, Yong; Li, Kai; Yang, Chuluo
Abstract: The practical use of luminescent mononuclear gold(I) complexes as optoelectronic materials has been limited by their inferior stability. Herein we demonstrate a strategy to improve the stability of gold(I) complexes which display thermally activated delayed fluorescence (TADF). A highly rigid and groove‐like σ‐donating aryl ligand has been used to form dual Au⋅⋅⋅H−C hydrogen bonds. The secondary metal‐ligand interactions have been authenticated by single‐crystal structure, NMR spectroscopy and theoretical simulations. The TADF Au I complex exhibits appealing emission properties (photoluminescence quantum yield=76 %; delayed fluorescence lifetime=1.2 μs) and much improved thermal and photo‐stability. Vacuum‐deposited organic light‐emitting diodes (OLEDs) show promising electroluminescence with a maximum external quantum efficiency (EQE) over 23 % and negligible efficiency roll‐off even at 10 000 cd m −2 . An estimated LT50 longer than 77 000 h with initial luminance of 100 cd m −2 reveals good operational stability. This work suggests a way for design of stable luminescent gold(I) complexes. Abstract : Robust mononuclear Au I emitters are prepared by harnessing intramolecular Au⋅⋅⋅H−C interactions. The new emitter displays appealing thermally activated delayed fluorescence (TADF) as well as thermal and photo‐stability, leading to high‐performance organic light‐emitting diodes with negligible efficiency roll‐off and good operational stability. This work shows the potential of secondary interactions for developing optoelectronic materials.